Construction safety management and engineering - Hill, Darryl C. (American Society of Safety Engineers, 2014)
"The new second edition of this ASSE best seller contains 38 chapters written by 42 contributors, and features new chapters on: Ladders, Ergonomics, and Construction Safety & Health through Design. Changes to the OSHA Construction Standard and other referenced Standards were made throughout, while five chapters were extensively revised: Insurance and Risk Management, Planning by Prevention and Design, Steel Erection, Industrial Hygiene, and Environmental Impacts. Written by construction safety experts and peer reviewed, the text focuses on best practices in hazard prevention, safe design, and recognition, assessment and control of physical and biological hazards and environmental impacts. The many illustrations throughout make the book useful for training, whether toolbox talks or classroom instruction. Construction Safety Management and Engineering is unique in its range of in-depth construction-related coverage, from insurance and risk management programs, safety training, prejob and pretask planning, electrical safety, ergonomics, and workzone safety/traffic control. There are a number of chapters of special interest including: Substance Abuse Programs for Construction Sites, Incident Investigation, and Safety and Your Spanish-Speaking Workforce"--Publisher's description